Historical changes in height, mass and age of USA women's Olympic gymnastics team: an update - Sands, W. A.; Murray, S. R.; McNeal, J. R.; Slater, C.; Stone, M. H. (Science of Gymnastics Journal, 2018)
Nearly every modern Olympic Games has brought astonished comments and criticism of the body sizes of female gymnasts. The comments from laypersons, scientists, journalists, and physicians too often imply that these diminutive athletes are unusually small and possibly unhealthy. Purpose: An extended and updated analysis of the sizes of U.S. female Olympic gymnasts including the 2012 and 2016 Olympic Games. Methods: Official public records from the US Olympic Committee and USA Gymnastics of Olympic team members were assessed including height, mass, age, body-mass index (BMI) and team performance rankings. Sixteen Olympic teams with a total of 123 team positions including the alternates were assessed. Trend analyses were conducted using linear and polynomial models. Results: Analyses indicated that since 1956, height, mass, age, and BMI declined at first and then increased, with the exceptions of height and rank. Best regression fits were obtained via 2nd order polynomial equations. Height and rank showed a downward trend throughout the historical period. Conclusion: Female Olympic gymnasts were getting smaller through approximately the 1980s and early 1990s. An upward trend in size variables was then observed through 2008. The addition of the 2012 and 2016 Olympic Games data showed that height shifted to a decline from a slight upward trend, and rank continued to decline throughout the historical period.